0118 Lifetime Occupational Exposure to Diesel Exhaust and Bladder Cancer among Men in New England. (23rd June 2014) - Koutros, Stella; Karagas, Margaret; Friesen, Melissa; Pronk, Anjoeka; Stewart, Patricia; Baris, Dalsu; Schwenn, Molly; Waddell, Richard; Johnson, Alison; Clerkin, Castine; Armenti, Karla; Colt, Joanne; et al.
Abstract : Objectives: We examined the association between lifetime occupational diesel engine exhaust (DEE) exposure and risk of bladder cancer in 1171 cases and 1418 controls in a population-based case-control study. Method: Lifetime occupational histories combined with additional exposure-oriented questionnaires were administered to obtain detailed information on DEE. We estimated the probability, frequency and intensity of exposure to respirable elemental carbon (REC) (μg/m 3 ), a primary surrogate for DEE. Unconditional logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs), adjusting for smoking and other risk factors. Results: DEE was associated with an increased risk of bladder cancer, with the highest level of cumulative REC (>252.8 μg/m 3 per year) having a 35% elevated risk (95% CI = 0.86–2.13) compared to those with no exposure. Among nonsmokers, we observed a significant trend in risk with increasing cumulative REC (p-trend = 0.03), with heavily exposed subjects having an OR=2.80 (95% CI =1.08–7.22). Time-period analyses by decade of first DEE-exposed job showed a statistically significant increased risk among men first exposed in the 1950s (heavily exposed: OR=2.73, 95% CI =1.29–5.79, p-trend = 0.009). Conclusions: The overall risk observed is modest, but similar in magnitude to those observed at comparable levels of exposure in previous studies of bladder and lung cancer. Greater risk for those first exposed in the 1950s may reflect secular trends in risk or a long latency for bladder cancer. Our results provide additional evidence that DEE is related to an increased bladder cancer risk.